Objects of Catholic Conversion in Colonial Buganda: A Study of the Miraculous Medal - Bennett, Alison 19XX- (Journal of religion in Africa, 2021)
Adorned with an image of the Blessed Virgin Mary and other Christian emblems and text, the miraculous medal has been an important object of Catholic intercessory prayer since the mid-nineteenth century. The religious and social history of the medal in Europe is relatively well known. However, few scholars have connected the medal’s emergence with the spread of the European mission in the wake of nineteenth-century colonial expansion. This article uses the medal to shed new light on the material, corporeal, and gendered aspects of the Catholic Christianization of present-day Buganda, where it fulfilled a variety of functions for missionaries and Baganda alike. For missionaries it served as a key item for proselytizing and propaganda. For some Baganda, meanwhile, it played pivotal roles in a newly emerging form of local religious identity politics. Object analysis of an extant version from Buganda also reveals the medal’s material diversity and offers important insight into local agency in the reception and reshaping of Catholic objects. Thus when viewed in non-European contexts, miraculous medals were far more dynamic and multifaceted than has previously been understood.